Problematika Implementasi Kebijakan Kota Bandar Lampung dalam Mewujudkan Ketentraman dan Ketertiban Umum: Perspektif Siyasah Dusturiyah - Hutasuhut, Ullynta Mona; Zuhraini, Zuhraini; Hermanto, Agus; Triono, Triono (Universitas Islam Negeri Raden Intan Lampung, 2022)
The local government of Bandar Lampung City has enacted Regional Regulation Number 1 of 2018 on Community Harmony and Public Order with the aim of creating a peaceful and orderly environment, especially for the people of Bandar Lampung. The government faces numerous challenges in addressing societal issues, such as the presence of informal businesses or street vendors (PKL) that disrupt public order, comfort, and the city's aesthetics. These vendors use public spaces like sidewalks meant for pedestrians, parking areas, and roadside areas for their businesses, causing disorder, traffic congestion, and littering due to waste disposal. This research is descriptive in nature, using qualitative methods. The findings indicate that the government has not been able to establish firm policies for implementing sanctions and providing guidance to the community and street vendors to achieve benefits without causing harm to any party. Therefore, the effectiveness of implementing Regional Regulation Number 1 of 2018 on Community Harmony and Public Order in Bandar Lampung City can be observed as functioning well. From a siyāsah dusturiyyāh perspective, the government has not been able to formulate clear policies to achieve benefits without causing harm to any party, as explained in the fiqh principles that all matters concerning the Muslim community should lead to what is good.